All-phosphorus flexible devices with non-collinear electrodes: a first principles study. Issue 10 (26th February 2018) - Li, Junjun; Ruan, Lufeng; Wu, Zewen; Zhang, Guiling; Wang, Yin
Abstract : The transport properties of all-phosphorus devices with non-collinear electrodes are studied using first principles. Abstract : With the continuous expansion of the family of two-dimensional (2D) materials, flexible electronics based on 2D materials have quickly emerged. Theoretically, predicting the transport properties of the flexible devices made up of 2D materials using first principles is of great importance. Using density functional theory combined with the non-equilibrium Green's function formalism, we calculated the transport properties of all-phosphorus flexible devices with non-collinear electrodes, and the results predicted that the device with compressed metallic phosphorene electrodes sandwiching a P-type semiconducting phosphorene shows a better and robust conducting behavior against the bending of the semiconducting region when the angle between the two electrodes is less than 45°, which indicates that this system is very promising for flexible electronics. The calculation of a quantum transport system with non-collinear electrodes demonstrated in this work will provide more interesting information on mesoscopic material systems and related devices.